3D cell-selex: seleção e caracterização in vitro de aptâmeros de RNA ligantes específicos às células tumorais prostáticas - Souza, Aline Gomes de (2015)
CHAPTER II: The human prostate cancer (PCa) is highly heterogeneous and multifactorial, and yet markers are not sufficiently accurate and none can predict the clinical outcome. Therefore, the search for new biomarkers for improved diagnosis, prognosis and therapy are still necessary. In this study, we describe the 3D Cell-SELEX, a strategy to select specific nucleic acid ligands against spheroid cells in 3D cell culture, which was performed against the PC-3 prostate cancer cell line. The new system combines the Cell-SELEX process that exploits the cellular structure to generate specific ligands, and the 3D cell culture that mimic the tissue microenvironment in vitro. The first round of 3D Cell-SELEX was performed against spheroids of the RWPE-1 non-tumor cell line to subtract aptamer ligands that are non-tumor specific. The supernatant was then used in eight additional rounds of selection, which were performed against spheroids of the PC-3 cell line. After nine selection cycles, eight PC-3 specific RNA aptamers were selected and sequenced, and presented sizes between 20 to 50 nucleotides-long, with low free energy (ΔG<-13.6), which confers spontaneous folding and high stability. This new strategy may provide a better exposure of extracellular domains in the membrane of the spheroid cultures, which specifically mimic the tumor microenvironment. The selected aptamers will be validated and applied in future studies focusing on the PCa management.